On Double Shell Formation Mechanism During Implosion of Plasma Puff Z-Pinches - Shmelev, Dmitry L.; Oreshkin, Vladimir I.; Zhigalin, Alexander S.; Rousskikh, Alexander G.; Chaikovsky, Stanislav A. (2020 7th International Congress on Energy Fluxes and Radiation Effects (EFRE), 2020)
This work presents the results of experimental and theoretical research of impact of tailored density profile and application of external axial magnetic field on its implosion dynamics. It has been discovered that upon implosion of the plasma metal puff Z-pinch some stripes interpreted as the system of two coaxial shells appear on the optical images. With the help of numerical simulation, the formation of the plasma liner consisting of a mixture of carbon and bismuth ions has been considered. It has been shown that the lightweight carbon ions facilitate formation of the density distribution smoothly decreasing with the increase in radius, that, in turn, leads to suppression of the Rayleigh-Taylor instability in the current sheath upon further implosion. It has also been demonstrated that availability of the two types of ions in plasma considerably different in mass leads to formation of a double shell with externally located heavy ions. It has also been revealed that the application of the external axial magnetic field leads to reduction in the plasma metal puff Z-pinch initial diameter.